Volunteer tourism outlook: an exploratory study on dive tourism operators in Kota Kinabalu, Sabah / Boyd Sun Fatt … [et al.] - Boyd Sun Fatt (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
Volunteer tourism seems to be gradually gaining its popularity and is currently a fast-emerging industry in Malaysia, particularly in Kota Kinabalu, Sabah. However, many previous studies merely explored its market niche and the various kinds of volunteer tourism issues. In addition, most of the studies concentrated on volunteer tourists, volunteer students and volunteer hosts. This study, therefore, was intended to explore the viewpoint of tourism players in particular the top management of dive tour operators with regards to volunteer tourism, and to know their involvement in a volunteer tourism programme that the dive tour operators had participated in. The results of this study illustrated that the significance of volunteer tourism is not only to the community and the environment but also to the country as a whole. Another highlighted part is location, cost, and time of the programme. The volunteer tourism programme is seen by the tour operators as beneficial to the community and host as well as the environment. The findings also show that volunteer tourism is an activity which includes travel and volunteer work without attempting to receive anything in return and this was fully understood by the top management of dive operators.